The project proposal of the CIHEAMMediterranean Research Network on Certification of Citrus (MNCC): the regional programme for the mandatory control of Citrus tristeza virus and its major vector Toxoptera citricidus in the Mediterranean region - D'Onghia A.M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
The Mediterranean citrus industry is faced with a major threat: citrus tristeza, a devastating virus disease whose very efficient vector, Toxoptera citricidus, has suddenly appeared in Northern Portugal and Spain. A very large proportion of the Mediterranean citrus orchards are still on sour orange; a root-stock highly sensitive to tristeza. With CTV inoculum present in almost all citrus producing countries, invasion of the Mediterranean region by T. citricidus will cause a rapid dissemination of CTV that will devastate all trees grafted on sour orange in a few years. A sudden collapse of the majority of the Mediterranean citrus industry will occur with unpredictable dramatic socio-economic consequences. The present project proposal aims at preventing such a disaster through a joint effort of all countries in the region for the implementation of urgent preventive and control measures against both the virus and its vector. The main steps of the work plan include: - enhancement of harmonized phytosanitary control measures and regulations (quarantine and certification); - CTV monitoring and characterization; - elimination of CTV-infected plants; - monitoring aphid population and implementing efficient control measures; - raising awareness; - strengthening of harmonized research and know-how; - technology transfer and information exchange.